2010
DOI: 10.1007/s12272-010-2222-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new 4,5-3(2H)pyridazinone derivatives and their cardiotonic, hypotensive, and platelet aggregation inhibition activities

Abstract: 4,5-dihydro-3(2H)pyridazinones such as CI-914, CI-930 and pimobendan along with tetrahydropyridopyridazine (endralazine) and perhydropyridazinodiazepine (cilazopril) have been used as potent positive inotropes, antihypertensives as well as platelet aggregation inhibitors. Accordingly, the present work involves the synthesis of 24 target compounds; 4,5-dihydro-3(2H)pyridazinones in addition to seven reported intermediates. The chemical structures of the new compounds were assigned by microanalysis, IR, 1H-NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
(17 reference statements)
0
14
0
Order By: Relevance
“…In a recent study, Amin et al . identified a few more pharmacophores necessary to elicit cardiotonic activity [60]. They found that carbonyl groups attached to the hydrazone greatly improved the cardiotonic activity of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Amin et al . identified a few more pharmacophores necessary to elicit cardiotonic activity [60]. They found that carbonyl groups attached to the hydrazone greatly improved the cardiotonic activity of the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiotonic, antihypertensive, and antiplatelet actions were also tested. The positive inotropic actions were exhibited that twelve of the compounds were exhibited higher effective responsesthan digoxin while eight of the compounds were less active than digoxin [78,79]. The triazole included 4, 5-dihydro-pyridazinones can be further modified to exhibit improved activity than the references drugs.…”
Section: Benzodioxanepyridazinonesmentioning
confidence: 99%
“…The synthesis of pyridazinone derivatives and investigation of their chemical and biological activities have gained more importance in recent years. Pyridazines and pyridazinones show wide spectrum of biological activities in the literature as potent inodilators (Kumar et al, 2010;Lee et al, 2010), vasorelaxants (Abouzid et al, 2010;Costas et al, 2010;Guerrero et al, 2008) and potent cardiotonic agents (Amin et al, 2008;Wang et al, 2009;. They showed also anticonvulsant (Edith et al, 2009;Sivakumar et al, 2009;Siddiqui et al, 2006), vasodilatory (Demirayak et al, 2009;Bansal et al, 2009), antihypertensive (Siddiqui et al, 2002;Ogretir et al, 2002;Vergelli et al, 2007), antimicrobial (Sotelo et al, 2002;Sayed et al, 2002), anti-inflammatory (Gokce et al, 2001;Dogruer et al, 2003;Frolov et al, 2004;Banoglu et al, 2004), anti feedant (Cao et al, 2003), herbicidal (Han et al, 2002), anti-nocieceptiv (Barbaro et al, 2002) activities.…”
Section: Introductionmentioning
confidence: 99%